A cooperative combined defense technique for jamming attack in MANET. (3rd March 2020) - Jayanand, A.
Mobile ad hoc networks (MANET) consist of continuously mobile nodes in the network. Due to this dynamic nature of the network, new nodes keep joining the network and some nodes exit the network every now and then. As a result, keeping track of every node in the network is not possible. So, malicious nodes like jammers can easily enter the network and affect the efficiency of the network. Hence, in this paper, we develop a cooperative combined defense technique for detecting jamming attacks in the MANET by determining the presence of jammers in the network. This is achieved by combining several important factors like correlation coefficient, carrier sensing time, packet delivery ratio (PDR) and signal strength (SS). Then a trust model is derived for each node and updated based on these measured parameters. Each node collaboratively checks the updated trust values of a suspected node and detects the jamming attack. Simulation results show that the proposed technique improves the detection accuracy and packet delivery ratio.